(untitled) (Perner’s Contacts, 2019)
The article was elaborated in connection with the diploma thesis (theme "Communication and conceptual network of roads in Pardubice"). the diploma thesis was led by Mrs. Ing. Michaela Ledvinová, Ph. D. and was elaborated at the Department of Technology and Control, Faculty of Transport Engineering of the University of Pardubice. the diploma thesis was awarded the Honorable Mention in the Competition for Best Diploma Thesis in the Area of Development (Jiřina Bergatt Jackson Award) and the prize of the chairman of the Jan Perner Foundation, and was recommended for publication in a professional journal. the article presents the proposed methodology, the methodology serves to determine the significance of the given road in the city.